LAW PROTECTION FOR DOMESTIC INDUSTRIES DUE TO DUMPING PRACTICE - Anita Kamilah (Faculty of Law, Universitas Jenderal Soedirman, 2015)
International trade is business transactions conducted across borders, which has the goal accumulated maximum profit (profit optimal). In this implementation, corporations often do business by unfair competition, such as dumping, which could damage the order of the importing country trading system. The problem is what factors are causing a corporation carrying out the practice of dumping, and also; and How is legal protection against a country as a result of dumping practices. Factors that cause dumping, to profit by setting lower prices in the import market and the monopoly in the market of the importing country. A form of protection for countries that suffered losses as a result of dumping practices which could impose